Evaluation of predatory function of Orius sauteri to the first-instar larvae of Mythimna separata (Walker) - YANG Haolan; LI Chengjun; CAO Fu; SUN Yulun; LI Maoye; LIU Su; LI Shiguang (浙江大学学报. 农业与生命科学版, 2023)
In order to know the control potential of Orius sauteri to the first-instar larvae of oriental armyworm [Mythimna separata (Walker)], the predation ability of the fifth-instar nymphs, male adults and female adults of O. sauteri to the first-instar larvae of M. separata was determined in the laboratory, and the Holling Ⅱ and Hassell-Varley models were used for analyzing the functional response, searching efficiency and mutual interference of O. sauteri to the first-instar larvae of M. separata. The results showed that the female adults of O. sauteri had the strongest predation ability to the first-instar larvae of M. separata (the ratio of instantaneous attack rate to handling time on single prey was 19.692), and their theoretical maximum daily predation was 19.231 individuals, and their handling time on single prey was the shortest (0.052 d). The male adults of O. sauteri had the moderate predation ability to the first-instar larvae of M. separata (the ratio of instantaneous attack rate to handling time on single prey was 16.610), and their theoretical maximum daily predation was 16.949 individuals, and their handling time on single prey was 0.059 d. The fifth-instar nymphs of O. sauteri had the weakest predation ability to the first-instar larvae of M. separata (the ratio of instantaneous attack rate to handling time on single prey was 13.211), and their theoretical maximum daily predation was 13.103 individuals, and their handling time on single prey was the longest (0.076 d). The daily predation of O. sauteri was positively correlated with prey density and negatively correlated with searching efficiency. The predation rate of O. sauteri on the prey decreased with the increase of predator density, while the intra-species competition intensity enhanced with the increase of predator density. In conclusion, O. sauteri has the potential to control the first-instar larvae of M. separata, of which the female adults work best.